Factors influencing students' entrepreneurial intentions: The critical roles of personal attraction and perceived control over behavior - Afsaneh Bagheri; Zaidatol Akmaliah Lope Pihie (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
Many researchers and educators across the world have recently attempted to explore the factors that motivate and enable some individuals and not others to pursue an entrepreneurial career path. The growing attentions given to entrepreneurial intention is partially due the fundamental roles that entrepreneurs and entrepreneurial activities play in fostering economic and social development of developed and developing countries, including Malaysia. Research has highlighted the influence of both personal and environmental factors on one's selection into entrepreneurship. More recent studies emphasized on the impact of a combination of the factors that affect entrepreneurial intention. However, our knowledge about interactions among the factors that construct entrepreneurial intention is limited particularly among university students. This study attempts to narrow the gap in the literature by measuring the factors that affect Malaysian university students' entrepreneurial intentions using the theory of planned behavior. More specifically, it examines the relationships between personal attraction, perceived control over behavior, entrepreneurial skills, subjective norms, valuation of entrepreneurship in the social and close environment and students' entrepreneurial intentions. The sample consisted of 722 students from public and private universities. Structural Equation Modeling was employed to test the hypothesized relationships between the variables. The results emphasized the critical roles that personal attraction and perceived control over behavior play in shaping students' intentions to become an entrepreneur. A system of valuation and support of entrepreneurship consisting of subjective norms and valuation of entrepreneurship in the social and close environment emerged which highly influences students' personal attraction toward entrepreneurship. Specifically, subjective norms affect students' entrepreneurial intentions through its impact on their perceived control over the performance of entrepreneurial tasks and personal attraction toward entrepreneurship. Furthermore, entrepreneurial skills have a low contribution to subjective norms and perceived behavioral control. Implications of these findings for entrepreneurship research and education are discussed.
Keywords: 650; Entrepreneurial intention; entrepreneurial skills; personal attraction; control over behavior